(3edGMXGJ Mhd GdcJGH GdeOQSj aj GdYGde GdYQHj (B: (3dHfGf, OQGSI MGdIs - (3LQGQ, SejQs ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2007)
(3jQi GdHGMK Cf gfGc KdGKI CfhGY ef GdcJGH GdeOQSj aj dHfGf gj(B: 1) (3GdcJGH GdeOQSj GdQSej GdPj JaQVg GdSdWI cJGHkG ehMOkG, (B2) (3GdcJGH GdeOQSj GdNGU, hgh cJGH Jbhe HEfJGLg OhQ GdfTQ hGdCHMGK GdhWfjI hJNVY gPg GdcJH dbQGAI ef bHd GdeQcR GdJQHhj ddHMhK hGdEfeGA hehGabJg, (B3) (3GdcJGH GdCLfHj gh cJGH JLGQj hVYJg OhQ fTQ CLfHjI, hjeJGR HOdjd ddeYde HGdEVGaI Edi JLgjRGJ hCOhGJ hTQGFM YdejI heQGLY(B... (3GdN(B. (3hjPcQ GdHGMK Cf GdeTcdI GdQFjSjI GdChdi GdJj hbY ajgG GdeQcR GdJQHhj ddHMhK hGdEfeGA aj dHfGf cGf GdLOhd GdRefj dEUOGQ GdcJH HMSH GdefGgL GdLOjOI(B. (3hCf GdeTcdI GdCcHQ gj Cf eYXe GdNHQGA GdPjf bGehG HJCdja GdcJH de jJHYhG GdefgLjI GdMOjKI aj JCdja gPg GdcJH, hCf eYXe GdSdGSd GdQSejI hGdhWfjI GdeWQhMI aj GdShb GddHfGfjI JaJbQ Edi COdI eYde PGJ aGFOI(B. (3hjYQV GdHGMK aj gPg GdOQGSI ebGQfI Hjf GdSdGSd GdCLfHjI hGdSdGSd GdJj Je EfJGLgG aj dHfGf, ajQi Cf Odjd GdeYde aj GdcJH GdCLfHjI jdYH OhQkG gGekG aj eSGYOI GdeYde, hCf gPg GdCOdI JbOe HQGeL Jbjje LQi JbfjfgG Ydi eSJhjGJ eNJdaI(B. (3dPdc jbJQM GdHGMK EfTGA eQcR YQHj (B"(3ddcJGH GdeOQSj(B" (3dJCgjd eLehYI ef GdeJNUUjf deSGYOI GdOhd aj EfJGL cJHgG(B. (3hbO YQV GdHGMK aj fgGjI GdOQGSI HWQjbI ehLRI CgOGa hfJGFL hJhUjGJ GdOQGSI GdJj bGeJ HgG GdgjFI GddHfGfjI ddYdhe GdJQHhjI HJbjje GdcJH GdeOQSjI Vef eTQhY Jbjje GdefGgL GdJYdjejI GdLOjOI aj dHfGf hGdPj TGQc aj QYGjJg GdeQcR GdJQHhj ddHMhK hGdEfeGA, hecJH GdjhfSch GdEbdjej aj HjQhJ heQcR GdCee GdeJMOI GdEfeGFjs
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Livres Scolaires; Textbooks; (3GdcJGH GdeOQSjs